Fanniidae - Dominguez, Martha Cecilia (2014)
The New Zealand species of the family Fanniidae are revised, and eleven valid species are recognized for this region: three adventive species (Euryomma peregrinum (Meigen), Fannia albitarsis Stein, Fannia canicularis (Linnaeus)), seven new species of the genus Fannia (Fannia anthracinalis n. sp., Fannia hollowayae n. sp., Fannia laqueorum n. sp., Fannia magnicornis n. sp., Fannia mangerensis n. sp., Fannia mercurialis n. sp., Fannia triregum n. sp.), and a monotypic new genus with the new species (Zealandofannia mystacina n. gen. and n. sp.). All new taxa are endemic to New Zealand and its surrounding islands. Descriptions and terminalia illustrations are provided for both sexes of all the species, where known. Keys for the New Zealand genera and species of adults and inmature stages of Fanniidae are given, and their geographic distribution is illustrated on maps.